The Causality of Economic Growth and Development of Telecommunications Infrastructure in ASEAN - ., Purwanti; Maya Nihayah, D (KnE Social Sciences, 2018)
The study aims to analyze the causality between development of telecommunications infrastructure and economic growth in ASEAN. The study uses annual time series data from ten ASEAN member countries for the period 1986-2015. The variables employed in this study are development of telecommunications infrastructure and economic growth which analyzed using granger causality test. The evidences show that there is unidirectional causality between development of telecommunications infrastructure and economic growth in Brunei Darussalam, Lao PDR, Myanmar, and Philippines in line with the views of SLH. Then Singapore shows bidirectional causality in accordance with the views of FBH. Indonesia, Cambodia, Malaysia, Thailand, and Vietnam in line with the views of NLH show no causal relationship between the two variables Keywords: telecommunications, infrastructure, economic growth, causality